The Utilization of Meta AI in Creating Educational Children's Story Illustrations - Misnawati Misnawati; Patrisia Cuesdeyeni; Alifiah Nurachmana; Linggua Sanjaya Usop; Albertus Purwaka; Sumiati Sumiati; Ruliyani Ruliyani; Anwarsani Anwarsani; Nabila Salwa; Levi Alkausar (Proceeding of the International Conference on Global Education and Learning, 2024)
This research aims to describe how Meta AI can be used in creating engaging and educational illustrations through children's stories, as well as analyzing its strengths and weaknesses. This study uses a descriptive qualitative approach to analyze the potential of Meta AI in making children's story illustrations. Data was obtained through: literature studies on Meta AI applications and trial illustration making using Meta AI. The results of the study show that Meta AI has great potential in producing illustrations that meet the needs of learning with high accessibility and creative exploration capabilities. However, limited contextual understanding, lack of human touch, and copyright issues are the main challenges. This study recommends collaboration between AI developers and human illustrators to optimize the quality of illustrations as well as training for educators in utilizing this technology.